HYBRIDISM IN CAMPURSARI MUSIC: AN AESTHETIC STUDY - Ramadhan, Bayu Gilang; Mauliska, Nur; Diamond, Jody (Universitas Islam Zainul Hasan Genggong, 2024)
Campursari represents a unique fusion between Western diatonic and Javanese pentatonic music. Its inception is rooted in the process of hybridity, a blending of diverse musical elements. In the realm of Indonesian music,